Conducting research with minimally verbal participants with autism spectrum disorder. (October 2017) - Tager-Flusberg, Helen; Plesa Skwerer, Daniela; Joseph, Robert M; Brukilacchio, Brianna; Decker, Jessica; Eggleston, Brady; Meyer, Steven; Yoder, Anne
A growing number of research groups are now including older minimally verbal individuals with autism spectrum disorder in their studies to encompass the full range of heterogeneity in the population. There are numerous barriers that prevent researchers from collecting high-quality data from these individuals, in part because of the challenging behaviors with which they present alongside their very limited means for communication. In this article, we summarize the practices that we have developed, based on applied behavioral analysis techniques, and have used in our ongoing research on behavioral, eye-tracking, and electrophysiological studies of minimally verbal children and adolescents with autism spectrum disorder. Our goal is to provide the field with useful guidelines that will promote the inclusion of the entire spectrum of individuals with autism spectrum disorder in future research investigations.